Brief report: the moderating effect of stress mindsets on associations between stress during pregnancy and symptoms of depression and anxiety. Issue 3 (4th May 2022) - Taouk, Laura; Schulkin, Jay; Gunthert, Kathleen
ABSTRACT: Background and Objectives: Research suggests that the extent to which stress is perceived as enhancing or debilitating can impact how stress is experienced, stress reactions, and stress-related outcomes. Given that there is a salient perception of stress as harmful during pregnancy, our aim was to investigate stress mindsets as a moderator of established associations between prenatal stress and elevations in anxiety and depression. Design: A survey design was used, yielding cross-sectional and longitudinal data. Methods: Participants ( n  = 388) completed a survey that included measures of stress, anxiety and depression, and stress mindsets during their pregnancy; a subset responded to a brief follow-up questionnaire assessing mental health outcomes six to eight weeks postpartum ( n  = 103). Results: Stress mindsets in pregnancy moderated the effect of perceived and pregnancy stress on prenatal anxiety and depression, as well as the effect of prenatal ratings of the pregnancy as a stressor on postpartum depression. The positive effect of stress on mental health outcomes grew stronger when stress was viewed as more debilitating, but was no longer significant when stress was viewed as more enhancing. Conclusions: Though further research is needed, a positive stress mindset could be protective against some of the negative effects of prenatal stress.